Digital orthodontic setup and clear aligners system for treating adult patients with periodontitis: a descriptive case report - Vincenzo Ronsivalle; Claudia Malara; Marco Cicciù; Piero Venezia; Antonino Lo Giudice (Frontiers Media S.A., 2024)
This case report describes the treatment of an adult female patient with a history of periodontitis (Stage 3 -Grade B) and presenting significant crowding in both maxillary and mandibular arches. After periodontal stabilization, the patient underwent orthodontic treatment with clear aligners (CAT) for less than one year. CAT provided an effective quantitative and qualitative control of the forces applied to resolve the malocclusion. This case report provides a detailed description of the clinical strategy and features associated with the clear aligners system which were considered ideal tools for treating periodontal patients during the decisional workflow. The orthodontic treatment goals have been successfully achieved considering functional, periodontal, and aesthetic expectations. Several characteristics of clear aligners could support the recurrence of this orthodontic system for treating patients with a history of periodontitis or at risk of periodontal damage.